Juridical Analysis of the Application of the Presumption of Innocence in Criminal Investigation - Simonda, Paulus Kostan; Muhibbin, Moh. (Universitas Islam Sultan Agung, 2023)
This study aims to determine the application of the presumption of innocence in the examination of criminal offenses. The type of research used is descriptive normative, with a statute approach, historical approach, conceptual, case and specific research. The results of this study indicate that the recognition of the presumption of innocence in the criminal procedure law applicable in our country contains two purposes. First, the provision aims to provide protection and guarantees to a human being who has been accused of committing a criminal offense in the process of examining a case so that his human rights are still respected. Secondly, these provisions provide guidance to officers to limit their actions in conducting examinations of suspects/defendants because they are human beings who still have the same dignity as those conducting the examination. One of the obstacles in the investigation process is that there are investigators who have not acted professionally in conducting investigations, resulting in actions that are contrary to the presumption of innocence.